Changes for Kirsten : a winter story - Shaw, Janet Beeler, 1937- (American girls collection., 1988)
A tough Minnesota winter brings many changes to Kirsten's frontier life, including the new responsibility of helping her brother Lars set his traps and a move into a new house for her family.